Fluorescence biosensor based on encapsulated quantum dots/enzymes/sol-gel for non-invasive detection of uric acid - Azmi, Nur Ellina; Ab Rashid, Ahmad Hazri; Abdullah, Jaafar; Yusof, Nor Azah; Sidek, Hamidah (Elsevier, 2018)
Non-invasive and simple method provides an alternative tool for the detection of uric acid in human biological sample without drawing a blood or puncturing the skin. This present work report a novel fluorescence biosensor based on sol-gel encapsulated CdS quantum dots (QDs)-Uricase/Horseradish Peroxidase (HRP) enzymes in 96-well microplate format. The QDs is used as fluorescence indicator to reveal fluorescence signal of the system resulting from the enzymatic reaction of uricase/HRP in the presence of uric acid. Upon addition of uric acid to the hybrid QDs-uricase/HRP, it will be oxidized to yield allaintoin, CO2 and H2O2. The produced H2O2 has the ability to quench the QDs fluorescence intensity which is proportional to the uric acid concentration. The developed microplate biosensor has shown its advantage in term of good system for simultaneously detection of 96 samples per assay within 20 min. The linear calibration curve towards uric acid was in the concentration range of 60–2000 µM with the detection limit of 50 µM. The developed sensor has successfully applied for the detection of uric acid in human urine and the results was comparable with the assay kit.